Penzion Pasohlávky - Madzik, Šimon (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Penzion se nachází na rovinatém pozemku na okraji Pasohlávek na břehu Věstonické nádrže. Navržený objekt se skládá ze dvou nadzemních podlaží. Stavba je rozdělena na dvě části. Jedna část je zimní zahrada spojená s restaurací a kuchyní, druhá část je obytná část se 2 jednotkami v prvním patře a 9 jednotkami ve druhém patře s celkovou kapacitou 26 hostů. Obytná část je uzavřena pro osoby navštěvující pouze restaurační část z důvodu většího soukromí. Penzion má několik parkovacích míst kolem budovy z přední strany pro návštěvníky nebo rezidenty. Kolem penzionu vede cyklostezka a nedaleký aquapark pro zpříjemnění pobytu obyvatel. Střechy jsou izolovány polystyrenem ISOVER EPS a minerální vlnou. Svislá nosná konstrukce domu je zděná z keramických tvárnic Porotherm s dodatečnou tepelnou izolací. Vodorovná nosná konstrukce je tvořena železobetonovými deskami. Stavba je postavena na betonových schodových základech. Druhé patro je po stranách tvořeno vazníky a střední část je tvořena ocelovým skeletem. Stěny ve druhém patře jsou provedeny z omítkových systémů Knauf.

The guesthouse is situated on a flat plot on the outskirts of Pasohlávky ashore of reservoir Věstonická nádrž. The proposed building consists of two above-ground floors. The building is divided into two parts. One part is winter garden connected with restaurant and kitchen, second part is residential part with 2 units on first floor and 9 units on second floor with a total capacity of 26 guest. The residential part is closed for the people visiting only restaurant area for providing more privacy. The guest house has multiple parking places around the building from the front side for visitors or residents. Around the guesthouse is cycling road and nearby waterpark for making residents stay more pleasant. The roofs are insulated by ISOVER EPS polystyrene and rockwool. The vertical load bearing structure of the house is masonry made of ceramic blocks Porotherm with additional thermal insulation. The horizontal load bearing structure is made of reinforced concrete slabs. The building is constructed on concrete step foundations. The second floor is made from roof trusses on sides and middle part is made from steel frame. The walls on second floor are made from Knauf plaster systems.
Guesthouse in Pasohlávky
Keywords: Penzion; šikmá střecha; keramické tvárnice.; Guest house; slope roof; ceramic blocks.